KARAKTERISTIK SUMBER FORMIL DAN MATERIL HUKUM ISLAM DI INDONESIA - Rusdi Sulaiman (Fakultas Syariah (Syari'ah Faculty ), 2020)
This paper aims to recognize the characteristics of the source of islamic law as represented by muhammadiyah fatwas, NU and MUI. Based on data analyzed with the method of content analysis, this paper concludes that textuality, which has long been pinned to Islamic jurists, is the main characteristic of the source of islamic law of the three fatwa institutions. In the Qur'an and hadith, NU prioritizes textuality as understood by the scholars of the Shafi'i School, while Muhammadiyah prioritizes the makbulah-an hadith. In the use of reason (ra'yu), the characteristics of the source of Islamic law of the three institutions are collectivity (collective ijtihad and scientific authority (professionalism). The main characteristic of the material source of Islamic law of the three institutions is good. Social beliefs and/or social customs ('urf) are characteristic of the material sources of Islamic law identified in Muhammadiyah and NU Fatwas, while subjugation to official authorities is identified in NU and MUI Fatwas, or subjugation via 'urf qanuni (